Influence of environmental conditions on accumulated polyhydroxybutyrate in municipal activated sludge. (1st April 2023) - Pei, R.; Tarek-Bahgat, N.; Van Loosdrecht, M.C.M.; Kleerebezem, R.; Werker, A.G.
Abstract: Poly(3-hydroxybutyrate) (PHB) was accumulated in full-scale municipal waste activated sludge at pilot scale. After accumulation, the fate of the PHB-rich biomass was evaluated over two weeks as a function of initial pH (5.5, 7.0 and 10), and incubation temperature (25, 37 and 55 °C), with or without aeration. PHB became consumed under aerobic conditions as expected with first order rate constants in the range of 0.19 to 0.55 d −1 . Under anaerobic conditions, up to 63 percent of the PHB became consumed within the first day (initial pH 7, 55 °C). Subsequently, with continued anaerobic conditions, the polymer content remained stable in the biomass. Degradation rates were lower for acidic anaerobic incubation conditions at a lower temperature (25 °C). Polymer thermal properties were measured in the dried PHB-rich biomass and for the polymer recovered by solvent extraction using dimethyl carbonate. PHB quality changes in dried biomass, indicated by differences in polymer melt enthalpy, correlated to differences in the extent of PHB extractability. Differences in the expressed PHB-in-biomass melt enthalpy that correlated to the polymer extractability suggested that yields of polymer recovery by extraction can be influenced by the state or quality of the polymer generated during downstream processing. Different post-accumulation process biomass management environments were found to influence the polymer quality and can also influence the extraction of non-polymer biomass. An acidic post-accumulation environment resulted in higher melt enthalpies in the biomass and, consequently, higher extraction efficiencies. Overall, acidic environmental conditions were found to be favourable for preserving both quantity and quality after PHB accumulation in activated sludge. Graphical abstract: Highlights: Intracellular PHB depolymerase activity can be constrained anaerobically. Changes in environmental conditions cause polymer loss even for short term storage. Extracellular depolymerase activity is limited if PHB remains intracellular. Acidic conditions are preferred to preserve quantity and quality for PHB recovery. The melting properties of PHB in the biomass may influence the polymer extractability.